Monitoring excimer laser-guided cardiac lead extractions by uniportal video-assisted thoracoscopy: A single center experience. (June 2022) - Wacker, Max; Thewes, Lena; Lux, Anke; Busk, Henning; Zardo, Patrick; Scherner, Maximilian; Awad, George; Varghese, Sam; Veluswamy, Priya; Wippermann, Jens; Slottosch, Ingo
Background: Though laser guided extractions of cardiac implantable electronic devices leads have become a routine procedure, the severe complications are associated with a high mortality. Here, we report our single center experience using uniportal video-assisted thoracoscopy for laser lead extraction and compare it to stand-alone laser lead extraction. Methods: The intraoperative data and postoperative clinical outcomes of patients undergoing laser lead extraction with concomitant thoracoscopy ( N = 28) or without ( N = 43) in our institution were analyzed retrospectively. Results: Neither the median x-ray time (612.0 s for the thoracoscopy group vs. 495.5 s for the non-thoracoscopy group, p = 0.962), length of the operation (112.5 vs. 100.0 min, p = 0.676) or the median length of hospital stay (9.0 vs. 10.0 days, p = 0.990) differed significantly. The mean intensive care unit stay was longer for patients in the non-thoracoscopy group (0.8 vs. 2.5 days, p = 0.005). The 30-day-mortality in the thoracoscopy group was zero, whereas five patients died in the non-thoracoscopy group. Furthermore, four patients in the non-thoracoscopy group had encountered haemothorax, while none were observed in the thoracoscopy group ( p = 0.148). Conclusions: The adoption of uniportal video-assisted thoracoscopy during laser-guided lead extraction of cardiac implantable electronic devices can be considered safe and does not lengthen the operating time or hospital stay. It might be useful in the detection of severe complications and, in experienced hands, possibly allow direct bleeding control.